Implementasi Metode Gravitasi Untuk Pemodelan Konseptual Sistem Panas Bumi Daerah Karaha-Talaga Bodas, Provinsi Jawa Barat - Ireneus Graharbarto; Herlienda Elizabeth Keilani Gagola; Kevin Febri Lantang Pasolang (Publikasi Indonesia, 2023)
The high usage of non-renewable energy and the uncertainty of heat sources in the Karaha- Talaga Bodas area are the background of this research. The high usage of non-renewable energy over-increased necessity can cause the reserve become depleted. Therefore, a different perspective is needed by switching the use of non-renewable to renewable energy, which is geothermal energy. To optimize the potential of geothermal, simillar research about geothermal’s system component is needed, which is heat source. This piece of information regarding the probability of the heat source being foreseeable from the surface, but the detail is still less-effective since most of the possible heat sources do not correspond to those indicated from the surface information, thereby, the gravity method can validating the probability of the heat source. The research purposely indicates the heat source and foresees the conceptual geothermal system in Karaha-Talaga Bodas area using the gravity method. The surface’s study results shows a probability of heat source as the eruption centers in the Karaha-Talaga Bodas area. The gravity’s study results shows a probability of heat source by the Bouguer anomaly, regional gravity anomaly, residual gravity anomaly, and high-density in the Talaga Bodas subsurface area. Meanwhile, the gravity’s study results shows a probability of heat source in Karaha subsurface by the residual gravity anomaly and high density contrast. Based on the conceptual model of Karaha- Talaga Bodas geothermal system, it can be interpreted that the geothermal system in Karaha and Talaga Bodas has different heat source.